RATING AND STUDY THE EFFECT OF SPONDYLOARTHROPATHIES FOR CHILDREN (World Bulletin of Public Health, 2022)
50 This paper aims to rate and study the effect of Spondyloarthropathies for children and were collected from different hospitals in Iraq in the analysis of spondyloarthritis in children in Iraq, and the patients were distributed to 35 boys and 15 girls. Two criteria were used: ILAR and AMOR, and the statistical value to the average age of patients according to the ILAR criterion was 6.9 ± 2.2 and the AMOR criterion 8.9 ± 3.1. As for the distribution of patients by gender (20 patients were boys and eight girls) according to the ILAR criterion, and the patients were distributed according to the AMOR criterion (15 patients were boys and seven girls). In this study, the diagnosis was based on MRI. Acute sacroiliitis was found in 18 patients, and inflammation of sacroiliac joints came in second place for 12 patients. Sacroiliitis is inflammation of the sacroiliac joints located in the back of the pelvis. It is rare in childhood and most common five to 10 years after the onset of the arthritis.